Modelagem 2,5D dos campos usados no Método Eletromagnético a Multi-Frequência - EMMF - SILVA, Valdelírio da Silva e (Universidade Federal do Pará, 2014)
This thesis shows the 2.5D calculation of synthetic data from the Multifrequency Electromagnetic Method (EMMF, from the portuguese name). The work is presented in two main parts: the first one presents the details of the numerical methods used in the calculation of the fields generated by the Horizontal Loop of Current, placed on the surface of bi-dimensional earth models; the second part uses the achieved results to simulate EMMF method data, which are the real and imaginary parts of the radial magnetic field from the loop. In the second part, we observe the computed fields from several different models, including variations in their physical properties as well as in the geometry of their features. We aim at estimating the sensibility of these fields to the structures that can be found in a sedimentary basin. With this modeling, we are able to study the characteristics of the data and to find how the two components of the radial field, real and the imaginary, contribute with separate and complimentary information about the structures in the models. The results show that the radial magnetic field presents very good lateral resolution, for a measure taken from a fixed source. The observed capability of these data to resolve target structures will be extremely important for the future work with the inversion of such data, as well as for the building of apparent resistivity sections.